Analytical and Chemometric Characterization of Sweet Pedro Ximénez Sherry Wine during Its Aging in a Criaderas y Solera System - Manuel J. Valcárcel-Muñoz; María Guerrero-Chanivet; María del Carmen Rodríguez-Dodero; Daniel Butrón-Benítez; María de Valme García-Moreno; Dominico A. Guillén-Sánchez (Foods, 2023)
Pedro Ximénez is a naturally sweet sherry wine produced in southern Spain from raisined Pedro Ximénez grape must and aged using a traditional Criaderas y Solera system. Complete analytical characterization has been useful in determining which parameters are the most influential in the aging of this wine. The organic acids, volatile compounds (higher alcohols, esters, aldehydes, and acetals), and phenolic compounds of this wine evolve during its aging, mainly through physico-chemical reactions and the contributions of wood compounds. During their aging, Pedro Ximénez sherry wines develop their organoleptic profiles, as tasting sessions have confirmed. A strong correlation between the aging of a wine and the parameters analyzed has also been corroborated through an MLR analysis. This allowed for the development of a model that, by using just 8 of the variables considered in the study, led to the determination of wine samples’ ages at over 97% confidence. This constitutes a rather useful tool for wineries to control Pedro Ximénez sherry wine aging processes.